Scientometric Mapping of Digital Transformation in Accounting and Finance - Judijanto, Loso (Westscience Press, 2025)
This paper performs an extensive scientometric analysis to delineate the global framework of digital transformation research in accounting and finance. The study utilizes Scopus data and analytical instruments, including VOSviewer and Bibliometrix, to investigate publication trends, prominent authors, institutional and international collaborations, and the conceptual framework of the field through keyword co-occurrence, network visualization, overlay mapping, and density analysis. The results show that there are various main topics, such as artificial intelligence, blockchain, machine learning, digital storage, and digitalization that focuses on sustainability. The results also show that the US, China, and European countries are leading strong global collaboration networks, and that growing Asian economies are making more contributions. The data shows that research on digital transformation is becoming more and more interdisciplinary, bringing together technological, economic, managerial, and socio-environmental points of view. The study offers theoretical and practical insights for academics, politicians, and practitioners, while also pinpointing research deficiencies and prospective avenues concerning advanced analytics, digital governance, and the alignment of international digital policy.